Effect of PGPB Secondary Metabolites in Inducing Systemic Resistance (ISR) and Enhancing Peroxidase Activity in Tomato Plants against Meloidogyne spp. Nematode Attack - Fahkrul Arifal; Yulmira Yanti; Eri Sulyanti; Rita Harni (Akta Agrosia, 2025)
Meloidogyne spp. nematode is important pathogen of tomato plants that causes a characteristic symptom, namely root knot. One alternative to controlling Meloidogyne nematodes is by utilizing PGPB secondary metabolites. The objective of this research is to explore the potential of secondary metabolites produced by PGPB in inducing systemic resistance (ISR) and increasing peroxidase enzyme activity in tomato plants attacked by Meloidogyne spp. This study used a completely randomized design (CRD), consisting of 11 treatments, 3 replicates. The observation parameters included Induced Systemic Resistance (ISR) Potential Test and peroxidase activity (PO) analysis. The results showed that the secondary metabolites from the Bacillus mycoides (MRSNUMBE.2.2) treatment were the best treatment in the ISR observation, which was indicated by the lowest nematode penetration rate, which was 3.66 nematodes in plant root tissue. In the observation of peroxidase activity, secondary metabolites from Bacillus waihenstephanensis (RBTLL.3.2) showed the highest peroxidase enzyme activity, which was 0.0437 µg/ml on day 7 and 0.0500 µg/ml on day 14. Keywords: induce systemic resistance, Meloidogyne spp., peroxsidase, secondary metabolites